Design of a reactive power droop control for generation system without inertia - Tian, Terence Peng Yu (2019)
In this report, a conventional Voltage-Reactive (V-Q) and Frequency-Power (F-P) droop are introduced in the microgrid. Renewable generation units connected to the microgrid introduces voltage and frequency instability into the system due to their intermittency. The droop control is developed and implemented to investigate the stability of the voltage and frequency using the conventional droop curve.